Plasma devices for ion beam and plasma deposition applications - Goncharov, A.; Demchishin, A.; Dobrovolskiy, A.; Kostin, E.; Panchenko, O.; Pavlov, C.; Protsenko, I.; Stetsenko, B.; Ternovoy, E.; Brown, I. G. (Вопросы атомной науки и техники, 2005)
We describe the operation of some new axially-symmetric plasma devices based on plasma-optical principles and the plasma lens configuration. Plasma devices of this kind using permanent magnets can be applied in a number of different applications for ion treatment and materials synthesis. Описуються деякі нові плазмові прилади, основані на використанні принципів плазмооптики та конфігурації плазмової лінзи. Прилади такого типу, що використовують постійні магніти, можуть застосовуватись для іонної обробки та отримання нових матеріалів. Описываются некоторые новые плазменные приборы, основанные на принципах плазмооптики и конфигурации плазменной линзы. Приборы такого типа, в которых используются постоянные магниты, могут применяться для ионной обработки и получения новых материалов.